O direito à dos adolescentes em privação de liberdade na Paraíba: Um estudo no Centro Socioeducativo (CSE) em João Pessoa – PB (2010 A 2014) - Silva, Vanya Araújo da (2016)
This work aims to reflect how adolescents who misdemeanors experience the right to education as fulfill socio-educational measure hospitalization. For both desk research based on cadastral records of 17 was held (seventeen) adolescents, as well as conducting interviews with each of them were serving detention measure in the Socio-Educational Centre in July and August 2015. It became also based on the observation of institutional space, which is the location of the work, as well as bibliographic and documentary research. In ethical terms, the research underwrote the new Resolution No. 466/12 of the National Health Council, getting approval from the Ethics Committee in Research UFPB as attached certificate. In this study, we discuss briefly the attention to children and adolescents in Brazil since the colonial period until the time of the Statute of the creation of the Children and Adolescents in 1990. Then, reflects on the state and the right to education, depending on its effectiveness can transform the lives of adolescents. Finally, it looks at how it has been granted the right to education in the inpatient unit of the Socio-Educational Center. From this study it was observed that education can play an important role in the lives of adolescents, since, besides the knowledge it provides, may favor the construction of a life project. Among the challenges identified is the fact of not having ensured that the adolescents continue their studies after completion of the measure.